Respostas
respondido por:
1
Explicação passo-a-passo:
f (2)= 3.2^2+10.2-3
f (2)= 3.4+20-3
f (2)=12+17
f (2)= 29
_______________________________
f (0)= 3.0^2+10.0-3
f (0)=0+0-3
f (0)=-3
_______________________________
f(-2)= 3.-2^2+10.-2-3
f(-2)= 3.4-20-3
f(-2)= 12-23
f(-2)=-11
_______________________________
f (1/2)=3.1/2^2+10.1/2-3
f (1/2)=3.1/4+10/2-3
f (1/2)=3/4+10/2-3
Tirando o mmc.=4
3+20-12=11
4 4
Creio que seja isto, espero ter lhe ajudado. Qualquer dúvida é só falar.
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás